Growth factors in multiple myeloma: a comprehensive analysis of their expression in tumor cells and bone marrow environment using Affymetrix microarrays - Mahtouk, Karène; Moreaux, Jérôme; Hose, Dirk; Rème, Thierry; Meißner, Tobias; Jourdan, Michel; Rossi, Jean François; Pals, Steven T.; Goldschmidt, Hartmut; Klein, Bernard (BMC cancer, 2010)
Multiple myeloma (MM) is characterized by a strong dependence of the tumor cells on their microenvironment, which produces growth factors supporting survival and proliferation of myeloma cells (MMC). In the past few years, many myeloma growth factors (MGF) have been described in the literature. However, their relative importance and the nature of the cells producing MGF remain unidentified for many of them.
Gesehen am 07.01.2022